Central Bank Independence: An Inevitable Choice for Sustainable Economic Governance - Sarker, Sujan; Karim, Rejaul; Halimuzzaman, Md. (RSF Conference Series: Business, Management and Social Sciences, 2025)
Central Bank Independence (CBI) has increasingly become a global policy norm, transcending variations in geography, political systems, and economic structures. While the theoretical literature highlights independence as a cornerstone of credible and effective monetary policy, empirical evidence from both advanced and emerging economies suggests that CBI plays a pivotal role in promoting price stability, controlling inflation, and strengthening macroeconomic resilience. This paper examines CBI through two critical dimensions, political independence and economic independence, and analyzes how these factors interact to shape institutional effectiveness. Drawing on comparative case studies and cross-country evidence, the study demonstrates that higher levels of CBI are strongly associated with sustainable economic governance and long-term fiscal discipline. The findings underscore that central bank independence is no longer a discretionary policy choice but rather an inevitable institutional requirement for safeguarding economic stability and credibility in the globalized era.